Analysis of The Influence of Promotion and Electronic Word of Mouth (E-WOM) on Membership Growth (Study of Araya Stable's Instagram Social Media 2025) - Agriphani, Agnes Pradipta Dyah; Wibowo, Sampurno (Dinasti Publisher, 2025)
This analysis investigates the effects of social media promotion and Electronic Word of Mouth (E-WOM) on member expansion at Araya Stable Yogyakarta in 2025. The rapid proliferation of social media and the efficacy of E-WOM as a marketing approach, especially in the expanding post-pandemic equestrian training sector, underpins this investigation. A descriptive quantitative methodology was utilized, with questionnaires given to 100 participants, encompassing prospective and current members of Araya Stable. The gathered data were processed using SPSS 15.0. The results indicate that social media impacts membership growth significantly, while E-WOM does not demonstrate statistically relevant influences. Combined, these two variables explain 25.7% of membership growth, with the balance influenced by other elements. Based on these findings, it is determined that refining social media promotional content is vital for attracting potential members, while E-WOM strategies need additional improvement. This study strives to offer practical suggestions to improve digital marketing effectiveness, consequently aiding the business growth of Araya Stable Yogyakarta.